Don Antonio hub a mixed used development linked to the MRT 7 Don Antonio Station - Espiritu, Olga Ianne D. (College of Architecture, University of the Philippines Diliman, 2017)
The construction of the Metro Rail Transit-7 (MRT-7) will surely trigger economic development at the areas it will traverse. New urban nuclei will soon emerge surrounding MRT-7's respective stations. The currently residential land use that is prominent at the areas near the future stations are bound to change just as what happened to the areas surrounding the MRT-3 and LRT stations. (Lapena, 2004) Don Antonio Station, one of the future MRT-7 stations, have observable existing lively urban activities. With proper planning and development of the area, this station could be turned into a Transport Oriented Development that would help revitalized the surrounding neighborhood. This design thesis, Don Antonio Hub, is a mixed used commercial building that provides commercial spaces, exhibit space and office spaces as derived from the commercial and office components of a Transport Oriented Development diagram. The commercial and exhibit spaces were designed with the residents in mind, who are mostly on-the go working people and students. This thesis also envisions that with the construction of the MRT-7, the Don Antonio Station's economic potential shall be maximized. It is projected to be the station that will host the most number of MRT-7 passengers going to the South, where the existing Central Business Districts are. (DoTr, 2003) If Don Antonio Station's potential as a Transport Oriented Development will be maximized, then Don Antonio won't only be the place to live, it will also be the place to relax, shop a nd work for its residents.